Computer assisted sperm analysis of Brahman crossbred breeding bull semen (Bangladesh Journal of Animal Science, 2017)
The present study was conducted at the Central Cattle Breeding and Dairy Farm, Saver, Dhaka from November 2015 to February 2016. Sixty ejaculates were collected from eight matured Brahman crossbred breeding bulls with a view to assess the motility and velocity parameters of ejaculates sperm using Computer-Assisted Sperm Analyser (CASA) with Andro Vision software. CASA parameters included as total motility (TM) (%), forward progressive motility (FPM) (%), fast motility (FM) (%) and circular motility (CM) (%); velocity parameters such as curvilinear velocity (VCL) (